Influence of Carbohydrates on Growth and Sporulation of Clostridium perfringens Type A - Labbe, Ronald G. (1975)
Growth and sporulation of Clostridium perfringens type A in Duncan and Strong (DS) sporulation medium was investigated. A biphasic growth response was found to be dependent on starch concentration. Maximal levels of heat-resistant spores were formed at a starch concentration of 0.40%. Addition of glucose, maltose, or maltotriose to a sporulating culture resulted in an immediate turbidity increase, indicating that biphasic growth in DS medium may be due to such starch degradation products. Amylose and, to a lesser extent, amylopectin resulted in biphasic growth when each replaced starch in the sporulation medium. A level of heat-resistant spores approximately equal to the control was produced with amylopectin but not amylose as the added carbohydrate. Addition of glucose or maltose to a DS medium without starch at stage II or III of sporulation did not alter the level of heat-resistant spores as compared with the level obtained in DS medium with starch. Omission of starch or glucose or maltose resulted in an approximately 100-fold decrease in the number of heat-resistant spores, although the percentage of sporulation (90%) was unaffected. The role of starch and amylopectin in the formation of heat-resistant spores probably involves the amylolytic production of utilizable short-chain glucose polymers that provides an energy source for the completion of sporulation.